Peran Globalisasi Dalam Membentuk Dinamika Ekonomi Nasional: Perspektif Ekonomi Politik - Candra, Mellyana; Clodya, Ferika; Sarlini, Heti; N, Norpaizah (Media Hukum Indonesia (MHI), 2025)
This study purpose to analyze the role of globalization in shaping Indonesia's national economic dynamics from a political economy perspective. The main focus is on how globalization influences economic policy, national economic structure, and its impact on public welfare. A qualitative approach with a literature review method is applied. Data sources were obtained from relevant scientific journals and literature published between 2020 and 2023. The analysis technique used content analysis on themes of globalization, national economy, and political policies. The findings indicate that globalization accelerates national economic growth through increased trade and investment flows. However, it also brings challenges such as social inequality, economic dependence on foreign markets, and pressure on domestic sectors. Politically, globalization fosters democratization and policy reform, though not all social groups benefit equally